Performance evaluation of electrical energy produced by polycrystalline silicon cells / Meloney Diva Patrick, Arica Ledumin and Siti Aminah Mohammad - Patrick, Meloney Diva; Ledumin, Arica; Mohammad, Siti Aminah (Universiti Teknologi MARA, Sabah, 2023)
Energy is the ability of a physical system to perform work. Energy exists in different forms such as heat, kinetic energy, mechanical energy, and light energy. Energy sources can be classified as renewable energy, which is naturally and constantly replenished, non-renewable energy that comes from resources that are being slowly replaced by natural processes. The aim of this project is to evaluate the performance of electrical energy produced by polycrystalline silicon (poly-Si) solar panels. Solar energy is a type of energy that generates electricity from the sun's heat. By utilising solar panel technology, electricity can be generated from solar energy. The most widely utilised technologies nowadays are mono- and poly-crystalline. This project involved arranging the poly-Si solar panels in both series and parallel circuits. As a result, the relationship between voltage and current is directly proportional in both circuits, and the maximum value of voltage was 2.22 V in the series circuit and 1.12 V in the parallel circuit. The results of this study have important implications for society, as solar energy has the potential to replace non-renewable sources as the main source of generating electricity. By reducing the use of non-renewable energy, we can mitigate pollution and its harmful effects on the environment.